Development of microbial desalination cells for the treatment of reverse osmosis reject water: a new benchtop approach - Dongre, Aman; Kothari, S.L.; Shami, Ashwag; Alsaad, Mohammad; Khan, Salah-Ud-Din; Abdull Razis, Ahmad Faizal; Khan, Shahanavaj; Poddar, Nitesh Kumar (Elsevier, 2024)
To address the growing global demand for usable water, there is an immediate necessity to enhance wastewater treatment systems. A continuous mode adaption of the conventional three-chamber microbial desalination cell (MDC) configuration was used, with gravity facilitating the flow of residential reject water for desalination. Initially, operating in batch mode with a 100 mL treatment volume, the single microbial desalination machine was expanded to 300 mL in continuous mode, capable of treating 5 L of home refuse water over 36 days. The batch mode MDC had a maximum current and power density of 3.81 µA/cm2 and 0.337 µW/cm2, resulting in 76 % desalination and 83.9 % COD eradication rates. Scaling up increased the MDC's performance, reaching a maximum of 0.45 µW/cm2 and 5.31 µA/cm2, which was 1.3 times greater than batch mode operation. The current work demonstrates the feasibility of microbial desalination cells and their novel approach for treating much higher quantities of reverse osmosis (R.O.) saline water in a comparable period of roughly 36 days. It emphasizes the actual limits when dealing with real-world wastewater samples, presenting a unique path for biotechnology by simultaneously generating bio-electricity and tackling future contaminants. Furthermore, incorporating desalination chambers with microbial fuel cells increases efficiency and opens up new options for enhanced wastewater treatment, resource recovery, and bioenergy generation. This pioneering strategy uses innovative membrane technologies and microbial optimization approaches to push the limits of desalination.